2017
DOI: 10.1155/2017/4323619
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adsorption of Selenium Ions from Aqueous Solution Using Iron Oxide Impregnated Carbon Nanotubes

Abstract: The aim of this research was to investigate the potential of raw and iron oxide impregnated carbon nanotubes (CNTs) as adsorbents for the removal of selenium (Se) ions from wastewater. The original and modified CNTs with different loadings of Fe2O3 nanoparticles were characterized using high resolution transmission electron microscopy (HRTEM), scanning electron microscopy (SEM), X-ray diffractometer (XRD), Brunauer, Emmett, and Teller (BET) surface area analyzer, thermogravimetric analysis (TGA), zeta potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…This result is consistent with the previous literature showing Freundlich fit for Se(IV) sorption using different sorbents such as layered double hydroxide (LDH) nanoparticle 39 and iron oxide impregnated carbon nanotubes. 16 …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with the previous literature showing Freundlich fit for Se(IV) sorption using different sorbents such as layered double hydroxide (LDH) nanoparticle 39 and iron oxide impregnated carbon nanotubes. 16 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Iron oxide impregnated carbon nanotubes showed the maximum Se(IV) adsorption capacity of 111 mg·g –1 , which is lower than that of Ca-alginate@citrus observed in the present study. 16 When compared to the maximum Se(IV) adsorption capacity of other adsorbents such as iron oxy-hydroxides, 42 Fe-metal organic framework (Fe-MOF) and Al-impregnated Fe-MOF (Al@Fe-MOF), 43 magnetite nanoparticles, 44 Fe 3 O 4 -chitosan nanocomposites, 45 MgO nanosheets, 46 and Fe/Si and Al/Si coprecipitate, 47 the citrus peels and Ca-alginate@citrus in the present study showed superior maximum biosorption capacity.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BET results for IOCS and ZVICS show increases since the irregular structure of the coated particles on the sand grains caused an increased surface area. Bakather et al 44 found that the removal of selenium (Se) by CNTs modified with 5%, 10% and 20% iron oxide nanoparticles increased due to increasing available sorption area, with apparent values of 226.6, 295.4, and 360 m 2 /g, respectively. Furthermore, Sharma et al 45 found that the iron sorption capacity onto coated sand appeared to be 10 to 55 times higher than that of the new sand due to the large specific surface area.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the chemical nonequilibrium TSM model was applied to estimate the nonequilibrium parameters, including Kf, 1/n, f and α for As(V) transport in the column experiments. The sum of square errors (SSE) and coefficient of determination (R 2 ) were used to assess the goodness of fit the curves 44 .…”
Section: Methodsmentioning
confidence: 99%